Reconstructing Land Acquisition and Compensation Policies for the Public Interest: Perspective on the Value of Justice in Indonesian Land Law - Rohmat, Noor; Rohmatika, Fiya Ainur (PT. Riset Press International, 2024)
This article discusses the reconstruction of land acquisition and compensation policies for the public interest from the perspective of the value of justice in the context of Indonesian land law. The research method used is qualitative, using literature study and document analysis as data sources. This approach allows for a deep understanding of the dynamics and challenges in land acquisition and compensation to affected land owners. In the context of policy reconstruction, this article analyzes the steps required, including identification of needs, evaluation of existing policies, and formulation of new policies or updating existing policies. Factors influencing the policy reconstruction process are also studied in depth, including political, economic, social, cultural and legal dynamics. In addition, this article highlights the mechanism for land acquisition for public purposes and the process of compensation to affected land owners. In this context, the perspective of justice values becomes the main focus, by evaluating ethical, moral aspects and principles of justice in providing compensation to land owners. This research is expected to provide an important contribution to understanding the importance of justice in the reconstruction of land acquisition and compensation policies for the public interest in Indonesia